Psychological Insights into the Impact of Yellowfin Fish Bone Powder and CaCO3 Therapy on Histological Features of Vertebrae Bone in an Ovariectomized Mice Model - Ahmad Talib, Suwarsih, Fitri Nurhidayati (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Introduction: The therapy of giving yellowfin tuna bone meal to experimental rats is one of the models used to determine the effectiveness of bone meal on changes in healing in ovariectomized rats. Treatment for osteoporosis to date only use provision of calcium as an ingredient for therapy for osteoporosis sufferers. Calcium is needed by the body to help the growth of bones and teeth. Purpose: This study aims to determine the effect of bone meal on histological features of vertebral bones in an ovariectomized rat model using yellowfin bone meal and Caco3. therapy. Methods: The method used in this study was an experimental study (experimental study) randomized post test control group design to determine the effect of surgical treatment (ovariectomy) and treatment of deproteinated, non-deproteinated yellowfin tuna bone meal and CaCO3 at a dose of (0, 400 , 800 and 1600 mg/kg BW/day) in ovariectomized rats. Results: The results showed that the greater the dose of yellowfin bone meal at a dose of 1600 mg/kg BW/day, the faster the vertebral bone repair towards healing, this was indicated by the bone thickness with the lowest value in the treatment and CaCo3 (63 mm); non-deproteinated (72 mm) and the highest was in the deproteinated treatment at a dose of 1600 (92.24 mm).